Profitability of stingless beekeeping production and beekeepers’ perception of extension agents’ performance - Isah, Ibrahim Aliyu (2018)
In business start-up a feasibility study is necessary to determine the profitability of the venture. Stingless beekeeping production has been found to be a profitable venture in Malaysia and to boost the production to a profitable level, knowledge and skills of the extension agents is very important for effective and efficient delivery of beekeeping technology and human resource development. Despite various government support in Malaysia, natural honey production is still insufficient to meet domestic demand. The trend lead to huge importation to satisfy the increasing demand for consumption. The study aimed at determining the profitability and level of stingless beekeeping production through technology transfer, human resource development and extension agents’ work performance, to examine relationship between technology transfer, human resource development and work performance, and to identify the most contributing factors to work performance of extension agents among stingless beekeepers in Malaysia. This research used quantitative research method. The questionnaires were analysed using capital budgeting analysis, descriptive statistics, correlation and regression coefficient analysis. Slovin formula was used to determine the sample size and Purposive sampling method was used to select 54 stingless beekeepers from ten stingless beekeeping state in Malaysia. The findings of the study indicate that the actual value of NPV in stingless bee project is positive, indicating the project may generate lucrative earnings in terms of assessment and bring more yield on investment when combined with the incentive schemes. In addition, the findings revealed that internal rate return (IRR) values indicating efficient yield of investment. Furthermore, the Profitability index revealed (PI) indicating the most profitable investment as it carries higher PI values and profit of more than RM1 from a single Ringgit invested in the stingless bee project. Also, the analysis on Pay Back Period (PBP) revealed the possible period within which to recover the initial money invested. Similarly, a sensitivity analysis was done to determine business risk analysis, the result indicate that even if there is increase in the hive cost and labour cost by 10%, 20% and 30% the project would remain profitable for investment and on the other hand, decrease in the selling price by 30% of the viability of stingless bee venture at the marginal value and still remain a lucrative venture and a feasible project. Results reveal two levels among stingless beekeepers on technology transfer, human resource development and work performance of extension agents; moderate (technology of stingless bee, dissemination of technology, evaluation of technology, leadership development, decision making and) and high (social skill). However, the work performance was at moderate level. The technology transfer and human resource development competencies all have positive correlation with work performance. The interpretation reads improvement in technology transfer and human resource development competencies of extension agents will lead to better work performance and will probably improve level of stingless beekeeping production and profitability among stingless beekeepers. However, three level of strength of relationship, dissemination, evaluation, decision making and leadership have strong positive correlation, whilst, social skill and technology have very strong and moderate positive correlation respectively. Respondents’ estimate coefficients performance model highlighted the significance of three variable of human resource development on extension agents’ work performance as shown by the score, Adj.R2 of 57.5%. Social skill was identified as the most contributing skill that influence extension agents’ work performance. This study contributes to a better understanding of the relationship of technology transfer and human resource development to work performance as they are genuinely important for any meaningful improvement in stingless beekeeping production in Malaysia.There is the need to create future development plan to improve the competency of extension agent in the Department of Agriculture particularly in the area of technology transfer and human resource development. Research institutes and Universities should embark on more research in the area of stingless bee technology and made available to farmers.